The ability of maintenance of static and dynamic balance in rhythmic gymnastics. Comparison of former elite gymnasts and no gymnasts - Skoura, D.; Tsopani, D.; Papouliakos, S.; Korres, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Balance is vital to many aspects of our daily lives and in rhythmic gymnastics the ability to maintain a stable position is indispensable for the implementation of every element of the sport ( Karpenko, 2003). The purpose of this research is to study the degree of balance capacity among former athletes skilled Rhythmic Gymnastics and non-athletes to determine whether and to what extent the special training in rhythmic gymnastics at high level develops the ability to balance. Methods: Participants were 35 female volunteers aged 19 to 25 years, divided into two groups. Experimental group: 15 were former elite gymnasts of rhythmic gymnastics and the control group: consisted of 20 participants who have not worked systematically in a sport. The measurements were made at an otolaryngology workshop of Medical School in Athens using a platform of computerised posturography for assessing the ability to balance (NeuroCom). A key test, Sensory Organization Test, reflects the overall coordination of the visual, somatosensory and vestibular systems that contribute to postural control ( Hans Chaundry, 2004). Other tests evaluated: motor adaptation to different vibrations of the platform, reaction time, movement velocity, directional control, on-axis velocity. Results: According to statistical data analysis it is shown that elite athlets excel in reaction time after auditory stimulus ( 0,5/1,1 sec), in movement velocity ( 2,4/6,8 deg/ sec) and in balance with swaying the environment and the surface ( 58,3%/51%) Discussion: The statistical results confirmed the initial hypothesis that elite athletes have better ability of balance probably due to the content of training in rhythmic gymnasts that includes quick reflexes and abilities to keep the balance under adverse conditions.